Tolley's corporate governance handbook - Chambers, Andrew (Butterworths Tolley CroydonGB, 2002)
Suggests best policies in the key areas of observance of best practices; public accountability; external and internal control & audit; board, board committee and director performance; risk management; fraud prevention; and sustainability.